Pesantren Feudalism or Ta'dzim? Contesting Western and Islamic Epistemologies in Digital Discourse. - Malik, Muhammad Umar Ibnu; Ramadhan, Tubagus Naufal; Syibromalisi, Alwi Akhmad (el-Tarbawi, 2026)
The digital era has intensified discursive contestations surrounding the kiai–santri relationship in pesantren (Islamic boarding schools). This study aims to map the dialectic between Western paradigms of feudalism and the Islamic tradition of ta'dhim (traditional reverence and obedience) within the digital public sphere. Employing a descriptive qualitative method and Fairclough’s critical discourse analysis, this study examines a limited empirical scope consisting of four viral social media contents and in-depth interviews with two key participants. The findings suggest that participants and pesantren-based narratives tend to frame ta'dhim not as a form of structural oppression, but rather as a mechanism of respect, identity formation, and a means of sustaining traditional values amid contemporary social change. Ultimately, this discursive interplay highlights how pesantren communities navigate traditional authority while adapting to modern decentralized digital spaces, suggesting a need for broader empirical exploration to fully capture these evolving dynamics.